Response inhibition is modulated by functional cerebral asymmetries for facial expression perception - Ocklenburg, Sebastian; Ness, Vanessa; Gunturkun, Onur; Suchan, Boris; Beste, Christian (Frontiers in Psychology, 2013)
The efficacy of executive functions is critically modulated by information processing in earlier cognitive stages. For example, initial processing of verbal stimuli in the language-dominant left-hemisphere leads to more efficient response inhibition than initial processing of verbal stimuli in the non-dominant right hemisphere. However, it is unclear whether this organizational principle is specific for the language system, or a general principle that also applies to other types of lateralized cognition. To answer this question, we investigated the neurophysiological correlates of early attentional processes, facial expression perception and response inhibition during tachistoscopic presentation of facial ‘Go’ and ‘Nogo’ stimuli in the left and the right visual field. Participants committed fewer false alarms after Nogo-stimulus presentation in the left compared to the right visual field. This right-hemispheric asymmetry on the behavioral level was also reflected in the neurophysiological correlates of face perception, specifically in a right-sided asymmetry in the N170 amplitude. Moreover, the right-hemispheric dominance for facial expression processing also affected event-related potentials typically related to response inhibition, namely the Nogo-N2 and Nogo-P3. These findings show that an effect of hemispheric asymmetries in early information processing on the efficacy of higher cognitive functions is not limited to left-hemispheric language functions, but can be generalized to predominantly right-hemispheric functions.